Studi Evaluasi Efek Samping Penggunaan Vaksin COVID-19 Terhadap Masyarakat Sebatik Timur: Study Evaluating the Side Effects of the Use of the COVID-19 Vaccine on the Eastern Sebatik Community - Lutfiatun Nisak; Juniza Firdha Suparningtyas; Hadi Kuncoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Vaccination is an effective prevention of disease transmission and an obligation to ensure the availability of vaccines, especially during this COVID-19 pandemic where the availability of vaccines has an Emergency Use Approvel (EUA) permit so that further research is needed on the effects. This study aims to see the effect of using the COVID-19 vaccine on people in East Sebatik. The research design used was a prospective non-experimental method with data collection techniques, namely purposive sampling. The subjects of this study were 100 people who were vaccinated against COVID-19 stage 1 and stage 2 in East Sebatik, especially those carried out by the East Sebatik Health Center. The result of this research is that the majority of respondents based on gender characteristics are women as many as 68 respondents (68%). The majority of respondents based on age characteristics are in the adult age group (26-45 years) as many as 54 respondents (54%). The majority of respondents based on the characteristics of the history of the disease were non-complicated as many as 67 respondents (67%). COVID-19 vaccine is currently restricted to age ? 18 years. The majority respondents based on side effect after the COVID-19 vaccine dose 1 was pain in the area of the injection site, which was 39 respondents (39%). And the majority of respondents based on side effect after COVID-19 vaccine dose 2 were 17 respondents (17%).